2019
DOI: 10.3390/math7050386
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effectiveness of Different Methods for Constructing Exact Solutions to Nonlinear PDEs. Generalizations and New Solutions

Abstract: The paper shows that, in looking for exact solutions to nonlinear PDEs, the direct method of functional separation of variables can, in certain cases, be more effective than the method of differential constraints based on the compatibility analysis of PDEs with a single constraint (or the nonclassical method of symmetry reductions based on an invariant surface condition). This fact is illustrated by examples of nonlinear reaction-diffusion and convection-diffusion equations with variable coefficients, and nonl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 79 publications
0
15
0
Order By: Relevance
“…Formulas (26) and equation (27) define the functional coefficients of equation (8) and its solution (2). It is noteworthy that for a(x) = a 0 x k , equation (27) admits the exact solution…”
Section: Some Generalizations and Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Formulas (26) and equation (27) define the functional coefficients of equation (8) and its solution (2). It is noteworthy that for a(x) = a 0 x k , equation (27) admits the exact solution…”
Section: Some Generalizations and Modificationsmentioning
confidence: 99%
“…Hence, in certain cases, it may be more effective than the nonclassical method of symmetry reductions based on an invariant surface condition. For details, see [26].…”
Section: Some Generalizations and Modificationsmentioning
confidence: 99%
“…The efficiency of all compared methods in terms of the maximum absolute global norm error versus the function evaluations is presented in Figure 5 for t ∈ [0, 30π]. For each algorithm, the most efficient step size control is used, if applicable, which for all embedded pairs is the modified algorithm presented in Equation (10). Otherwise, a constant step is used.…”
Section: Resultsmentioning
confidence: 99%
“…The analytical solution of the NLS with varying coefficients has attracted great interest in the recent past (e.g., see [5][6][7] or more recent works in [8][9][10][11] and references therein). Additionally, the computation of the NLS is a critical part of the verification process of the analytical theories.…”
Section: Introductionmentioning
confidence: 99%
“…This method allowed to find more than 40 exact solutions of nonlinear reaction-diffusion equations and wave type equations with variable coefficients involving one or more arbitrary functions. In [36], it was shown that some of the solutions given in [34,35] cannot be obtained using the nonclassical method of symmetry reductions [38][39][40][41][42][43][44][45] (see also [18,23]) based on the use of the invariant surface condition (a first-order differential constraint equivalent to the relation (4)). Note that constructing solutions in implicit form with the integral term (4) often allows us to reduce the order of the resulting functional differential equations [33,34].…”
Section: A Brief Overview Of Modifications Of the Methods Of Functionamentioning
confidence: 99%